Factors affecting retained fetal membrane and its therapeutic management in dairy cows (International Journal of Natural Sciences, 2016)
Retention of fetal membrane (RFM) in dairy cows is a common complication after parturition due to failure of the separation of villi of fetal cotyledon from crypts of maternal caruncles and affects on reproductive cycle. The present study was conducted in 594 cows of 15 different dairy farms of Sylhet district. The data was collected by direct interviewing of the farmers in a prescribed questionnaires data sheet and data record from the register of the contracted farms. The overall incidence of retained placenta was 17.51 %.The cross bred dairy cows had higher incidence (14.14%) of RFM compared to local one (3.04%) and differ significantly (p